New rules are not rules: Privatization of pastoral commons and local attempts at curtailment in southwest Madagascar - Johanna Friederike Goetter; Regina Neudert (International Journal of the Commons, 2016)
This paper examines the case of indigenous privatization of the important fodder tree samata (Euphorbia stenoclada) and concurrent legal curtailment of this privatization among the Tanalana people of southwest Madagascar from a long-term perspective. Applying a framework for institutional change to empirical data derived from interviews conducted in 20 villages in the Mahafaly Plateau region, the study explores the process and mechanisms involved in creating and asserting private property rights to this common pool resource on the one hand, and the process of curtailment on the other. Implementation of the curtailing institutions is hampered by (1) the low bargaining power of village communities versus privatizers, which stems from the users’ preference for avoiding open conflicts and laissez faire ideology, (2) the low social acceptance and internalization of new curtailment rules, which are perceived as contradictory to customary resource privatization rights and the ideology of personal freedom restricted only by ancestral rules-in-use, and (3) ineffective self-governance and enforcement mechanisms based on pro-active monitoring of local users. Stressing the interplay between ideology and bargaining power in the context-specific constellation of actors, this paper contributes to the understanding of the transformation of property rights and institutional change in self-organized, traditional societies.